2023
DOI: 10.3390/polym15061540
|View full text |Cite
|
Sign up to set email alerts
|

Computational Exploration of Bio-Degradation Patterns of Various Plastic Types

Abstract: Plastic materials are recalcitrant in the open environment, surviving for longer without complete remediation. The current disposal methods of used plastic material are inefficient; consequently, plastic wastes are infiltrating the natural resources of the biosphere. The mixed composition of urban domestic waste with different plastic types makes them unfavorable for recycling; however, natural assimilation in situ is still an option to explore. In this research work, we have utilized previously published repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…75 Amongst the features evaluated, including monomer chemistry, polymer architecture, molecular weight distribution and crystallinity, the chemical nature of the backbone linkage was reported to be the most important parameter in determining the biodegradation profile of a polymer. Separately, a literature-driven cluster analysis 130 was performed using the PlasticDB database to identify a relationship between various polymers and their biodegradation profiles. Curated from 471 publications, the results demonstrated that the chemical classification, and hence the structure of the polymer backbone, has a direct relationship to its susceptibility to biodegradation.…”
Section: Strategies For the Design Of Biodegradable Polymersmentioning
confidence: 99%
“…75 Amongst the features evaluated, including monomer chemistry, polymer architecture, molecular weight distribution and crystallinity, the chemical nature of the backbone linkage was reported to be the most important parameter in determining the biodegradation profile of a polymer. Separately, a literature-driven cluster analysis 130 was performed using the PlasticDB database to identify a relationship between various polymers and their biodegradation profiles. Curated from 471 publications, the results demonstrated that the chemical classification, and hence the structure of the polymer backbone, has a direct relationship to its susceptibility to biodegradation.…”
Section: Strategies For the Design Of Biodegradable Polymersmentioning
confidence: 99%
“…Thermochemical treatment and land filling are the primary means of plastic disposal, however biological deconstruction for renewable plastic generation or other bio-products are being investigated (Bertocchini and Arias, 2023;Malik et al, 2023). Recycling and up-cycling plastics to biodegradable plastics bioproducts are two approaches that can help restore the damage caused by this polymer (Kochanska et al, 2022;Morici et al, 2022).…”
Section: Wet Wastes and Plasticsmentioning
confidence: 99%
“…Plastic waste has become a significant threat to the environment, with millions of tons of plastic ending up in oceans and landfills every year [3]. The problem with plastic waste is that it takes hundreds of years to decompose, and it often ends up in landfills or oceans, causing harm to wildlife and the environment [4]. This has led to a massive accumulation of plastic waste in our landfills, oceans, and water bodies [5].…”
Section: Introductionmentioning
confidence: 99%